Salivary Biomarker in Diagnosis of Oral Squamous Cell Carcinoma: A Scoping Review - Sadat, S M Anwar; Akther, Liza (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Oral saliva is an extracellular fluid produced and secreted by salivary glands which contains 99% of water and 1% of organic and inorganic substances. Inorganic elements consist of minerals such as sodium, potassium, calcium, magnesium, fluoride, and phosphates. Organic elements comprise enzymes, hormones, immunoglobulins, antioxidants are present in the saliva. The recent findings suggest that saliva could be used as a biomarker in diagnosing oral cancer and pre cancer. Most oral cancers are oral squamous cell carcinomas. Using saliva for detection of early oral squamous cell carcinomas in the search for new clinical markers is a promising approach because of its noninvasive sampling and easy collection method. Biomarkers are the molecular signatures and indicators of normal biological, pathological process, and pharmacological response to treatment hence may provide useful information for detection, diagnosis, and prognosis of the disease. This review article provides the up-to-date list of known and emerging potential salivary biomarkers for diagnosis of oral cancer and pre cancer. Salivary biomarkers will help to differentiate patients who clinically have no detectable disease but are potential candidates for oral cancer. J Bangladesh Coll Phys Surg 2025; 43: 294-297